Reduced indinavir exposure during pregnancy. (20th August 2013) - Cressey, Tim R.; Best, Brookie M.; Achalapong, Jullapong; Stek, Alice; Wang, Jiajia; Chotivanich, Nantasak; Yuthavisuthi, Prapap; Suriyachai, Pornnapa; Prommas, Sinart; Shapiro, David E.; Watts, D. Heather; Smith, Elizabeth; et al.
<x xml:space="preserve">Abstract</x> Aim To describe the pharmacokinetics and safety of indinavir boosted with ritonavir (IDV/r) during the second and third trimesters of pregnancy and in the post‐partum period. Methods IMPAACT P1026s is an on‐going, prospective, non‐blinded study of antiretroviral pharmacokinetics (PK) in HIV‐infected pregnant women with a Thai cohort receiving IDV/r 400/100 mg twice daily during pregnancy through to 6–12 weeks post‐partum as part of clinical care. Steady‐state PK profiles were performed during the second (optional) and third trimesters and at 6–12 weeks post‐partum. PK targets were the estimated 10th percentile IDV AUC (12.9 μg ml−1 h) in non‐pregnant historical Thai adults and a trough concentration of 0.1 μg ml−1, the suggested minimum target. Results Twenty‐six pregnant women were enrolled; thirteen entered during the second trimester. Median (range) age was 29.8 (18.9–40.8) years and weight 60.5 (50.0–85.0) kg at the third trimester PK visit. The 90% confidence limits for the geometric mean ratio of the indinavir AUC(0, 12 h) and Cmax during the second trimester and post‐partum (ante : post ratios) were 0.58 (0.49, 0.68) and 0.73 (0.59, 0.91), respectively; third trimester/post‐partum AUC(0, 12 h) and Cmax ratios were 0.60 (0.53, 0.68) and 0.63 (0.55, 0.72), respectively. IDV/r was well tolerated and 21/26 women had a HIV‐1 viral load < 40 copies ml−1 at delivery. All 26 infants were confirmed HIV negative. Conclusion Indinavir exposure during the second and third trimesters was significantly reduced compared with post‐partum and ∼30% of women failed to achieve a target trough concentration. Increasing the dose of IDV/r during pregnancy to 600/100 mg twice daily may be preferable to ensure adequate drug concentrations.